Evidence-based nursing intervention to reduce skin integrity impairment in children with diaper dermatitis: A systematic review - Prihatini Dini Novitasari; Dessie Wanda (PAGEPress Publications, 2021)
Diaper dermatitis often occurs in children. In Indonesia, the guidelines for managing this health problem are issued by each hospital in Indonesia, but there are no guidelines for formal prevention and management released by the Indonesian Health Ministry. This study aimed to propose the Air, Barrier, Cleansing, Diapering, Education (ABCDE) approach as an evidence-based independent nursing intervention to prevent and treat impaired skin integrity, particularly diaper dermatitis, in children by nurses. This systematic review was derived from multiple databases using the following keywords: "child," "diaper dermatitis," "diaper-free time," "air," "barrier," "cleansing," "diaper," and "education." From these keywords, 393 articles were collected and then filtered using inclusion and exclusion criteria to obtain the final articles to be analyzed. Thirty-one articles passed the criteria. The study found that the ABCDE approach was effective in preventing and treating diaper dermatitis in children. Its indicators of the approach were preventing or decreasing inflammation, repairing damage to the skin, and preventing reoccurrence. Based on the review and analysis of multiple aspects in Indonesia, the authors proposed a modification of the sequence to CBAD-E to implement the approach in Indonesian children. The intervention of the ABCDE approach matches Indonesian children's situation, and therefore it can be implemented in Indonesia. Accordingly, this recommendation may be useful and feasible to be implemented by nurses in preventing and treating diaper dermatitis in children, thus decreasing its prevalence.